Sensory acceptance of food developed for older adults in different settings. Issue 2 (6th January 2021) - Svendsen, Jonas Anias; Okkels, Signe Loftager; Knudsen, Anne Wilkens; Munk, Tina; Beck, Anne Marie
Abstract: Nursing home residents and patients discharged from hospital are at high risk of malnutrition. Their nutritional status could possibly be improved by identifying and serving meals according to their preferences. The aim of the present study was therefore to test the sensory acceptance of a culinary improved meals‐on‐wheels menu developed for nursing home residents in two other settings with different participants. The participants (52 in a nursing home setting, 527 in an outpatient setting and 25 in a home setting) evaluated liking of appearance, flavor, and texture on a five‐point liking scale. A value of 3.5 was selected to evaluate if a certain hedonic aspect was accepted. The results showed that all meals in the culinary improved menu were well‐liked. Still, we did see that some of the meals were rated below 3.5, probably because of age‐related differences and/or the context of the study settings. Hence, for future studies, different levels of culinary adjustments of these meals could be investigated to find the optimal level, still making the meal a stimulating experience. Practical application: This study demonstrated how small, fortified and familiar meals might successfully be applied to improve the nutritional status of a broad group of older adults. When creating a menu for older adults, you need to consider the portion size, the energy and protein content as well as the preferences of older adults. Meal tasting sessions with older adults can be used to gain insight into meal preferences and target product development to improve food intake.